Submission Instructions - Revista de Direito Civil Contemporâneo, (Revista de Direito Civil Contemporâneo, 2023)
The Journal of Contemporary Private Law, ISSN 2358-1433, published quarterly by Editora Revista dos Tribunais, in Brazil, invites academics and researchers to submit unpublished papers for its first issue of 2015, in the following areas: a) jurisprudence related to private law; b) history of private law; c) roman law; d) comparative private law; e) the law of obligations; f) contracts; g) torts; h) property law; i) family law; j) probate and succession law. [...]